Designing for an Uncertain Future: Rural Urban Framework, Shichuang Village House Prototype, Guandong Province, China. (July 2016) - Lin, John
Abstract : Recent decades in rural China have seen a dramatic shift from traditional courtyard house s that could be extended horizontally, to standardised concrete‐frame constructions on limited plots that can grow only upwards. As the rural‐urban divide disintegrates, the rural needs to be redefined. Guest‐EditorJohn Lin of Rural Urban Framework outlines the practice's proposals for a vertical core that could utilise government subsidies to offer a more diverse, flexible development model for village life.